Metacognitive Ability and the Precision of Confidence - Somatori, Keita; Kunisato, Yoshihiko (Frontiers in Human Neuroscience, 2022)
In prior research, signal detection theory (SDT) has been widely utilized to assess metacognitive ability. However, SDT metacognitive model requires the use of a two-alternative forced-choice task, while confidence must also be measured discreetly. In said model, participants' cognitive ability and their confidence in the cognitive task were used to estimate their metacognitive abilities. Therefore, in this study, a metacognitive model that can be applied to various cognitive tasks was developed. This model implements item response theory and Q-learning models to estimate cognitive potential; in this model, participants' metacognitive ability is defined as the correspondence between their confidence in their cognitive ability and their actual cognitive ability. The entire procedure was divided into two experiments. In experiment 1, two different cognitive tasks were used to estimate metacognitive ability and to examine overall discriminative and convergent validity. Notably, the parameters representing metacognitive ability did not correlate with cognitive ability but were positively correlated between the two tasks. In experiment 2, we performed a similar analysis using a different task to test the replicability of experiment 1. The results for experiment 2 were replicated for discriminative and convergent validity, albeit with weak results. Our metacognitive model exhibited high interpretability and versatility.